2013
DOI: 10.1164/rccm.201210-1937oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung Microbiota and Bacterial Abundance in Patients with Bronchiectasis when Clinically Stable and during Exacerbation

Abstract: Rationale: Characterization of bacterial populations in infectious respiratory diseases will provide improved understanding of the relationship between the lung microbiota, disease pathogenesis, and treatment outcomes. Objectives: To comprehensively define lung microbiota composition during stable disease and exacerbation in patients with bronchiectasis. Methods: Sputum was collected from patients when clinically stable and before and after completion of antibiotic treatment of exacerbations. Bacterial abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
214
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(244 citation statements)
references
References 61 publications
10
214
0
8
Order By: Relevance
“…31 The differences between microbial communities were investigated by nonmetric multidimensional scaling (NMDS), which was based on weighted UniFrac dissimilarity among samples. 32,33 The ordination axes explain variance in the dissimilarities. 33 Statistical Analyses.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…31 The differences between microbial communities were investigated by nonmetric multidimensional scaling (NMDS), which was based on weighted UniFrac dissimilarity among samples. 32,33 The ordination axes explain variance in the dissimilarities. 33 Statistical Analyses.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…ALlthough the agreement between the presence and absence of bacteria detected by culture and sequencing was relatively good for some aerobic bacteria, it was extremely poor for several other aerobic bacteria (Haemophilus, Staphylococcus, and Streptococcus) and anaerobic genera (such as Prevotella and Veillonella). Samples obtained during exacerbations had an increase in anaerobic microbes relative to aerobic microbes, suggesting that this compositional change may be an important factor contributing to the onset of exacerbations missed by culture techniques (78).…”
Section: Lessons Learned From the Study Of Airway Microbiota In Lung mentioning
confidence: 99%
“…Our major findings are consistent with literature reports. Using anaerobic culturing and 16S ribosomal ribonucleic acid pyrosequencing, Tunney et al 22 found that microbiome taxa (predominantly Proteobacteria) abundance remained relatively constant during bronchiectasis exacerbations and convalescence, suggesting that changes in bacterial density are unlikely to account for bronchiectasis exacerbations. The increased systemic inflammation during exacerbations could be abrogated by antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertonic saline (3-5%) induction was applied, as appropriate. 22 Samples with Ն25 leukocytes and Յ10 epithelial cells under microscopic field (ϫ100) were deemed eligible.…”
Section: Sputum Sampling and Bacterial Culturementioning
confidence: 99%